Evaluation of colour vision according to type of implanted artificial foldable intraocular lens - Stopyra, Wiktor (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: The aim of research was comparing the colour vision of patients with blue light filtering artificial lens to the patients with implant without blue light filter. Material and methods: 99 patients (120 eyes) divided on three groups were examined. 40 patients (40 eyes) after cataract surgery with implantation of blue light filtering lens were the first group. 39 patients (40 eyes) who had implanted lens without filter were the second group. 20 patients (40 eyes) with own transparent lens were the third group. Farnsworth-Munsell 100 Hue test was used in research. Each patient made test on thirtieth day after cataract surgery. Results: Following average total error score (TES) values in groups were observed: the first group – 60.66, the second group – 83.71, the third group – 61.55. Average axis of disorder in blue-yellow range was following: patients after cataract surgery with implantation of blue light filtering lens – 5.48, patients with implant without blue light filter – 7.28, control group – 5.74. Conclusions: 1. Kind of artificial intraocular lens has meaning in colour vision at pseudophakic patients. 2. Blue light filter of artificial intraocular foldable lens advantageously effects perception of colours. 3. Lack of blue light filter in artificial intraocular lens gets worse colour vision especially in blue-yellow range.